Investigation Of The Factors Affecting The Success Of Vestibular Rehabilitation Therapy In Patients With Idiopathic Unilateral Vestibular Hypofunction And Idiopathic Bilateral Vestibular Hypofunction - Ertugrul, Suha; Soylemez, Emre (ENT Updates, 2019)
Objective: The aim of this study was to determine the factors affecting the success of vestibular rehabilitation therapy (VRT) in patients with idiopathic unilateral vestibular hypofunction (UVH) and idiopathic bilateral vestibular hypofunction (BVH). Methods: 30 patients with idiopathic UVH and 30 patients with idiopathic BVH were included in this prospective study. Visual analog scale (VAS) was used to evaluate the severity of the patients’ complaints of dizziness. The duration of the complaint of dizziness was recorded. All patients underwent the Dizziness Handicap Inventory (DHI) before and after VRT. The severity, duration, and localization (unilateral/bilateral) of the vestibular hypofunction were compared with the efficacy of VRT. Results: A significant decrease in DHI scores was observed after VRT for both, UVH and BVH patients, as compared to their pre-VRT scores (p<0.001). There was no significant difference in the efficacy of vestibular rehabilitation therapy in patients with UVH and BVH (p=0.09). As the VAS scores increased and the duration of the complaint lengthened, the efficacy of VRT decreased significantly (p<0.001/r=5.6, p=0.016/r=3.1, respectively). Conclusion: VRT is an effective treatment for the relief of symptoms in both UVH and BVH patients. Unilateral or bilateral vestibular hypofunction does not affect the efficacy of VRT, whereas prolonged or severe symptoms of dizziness affect the effectiveness of VRT negatively. In idiopathic vestibular hypofunction patients with long-standing and/or severe dizziness complaints, VRT should be initiated immediately and continued longer.